Smart book reader for visual impairment person using IoT device - Harum, Norharyati; Zakaria, Nurul Azma; Emran, Nurul Akmar; Ayop, Zakiah; Anawar, Syarulnaziah (The Science And Information Organization (SAI), 2019)
This paper focuses on development of Smart Book Reader will help the blind people or who have low vision to read the book without using braille. This project utilises IoT technology with the use of an IoT device, IoT infrastructure and service. An IoT device, Raspberry Pi, is used which is very energy efficient because it only uses 5V of power to run. It is also a high portability device with only credit card size and can be carried out anywhere. Book reader will capture the picture of book pages using camera and book reader will process the images using Optical Character Recognition software. When the image is recognised, book reader will read it aloud1. Therefore, the blind people or those who have low vision will hear it without needing to touch using their fingertips. By using this book reader, the user can enjoy both softcopy and hardcopy books, by using online text to voice converter with a help of IoT connectivity protocol such as Wifi and 4G services. For hardcopy book, a camera is embedded to capture the page. The motivation to develop this product is to encourage all blind people to read ordinary books. This will help them to gain particular knowledge from the reading without a need to learn Braille.